Compliance with Fe Tablet Consumption and Anemia Incidence in Pregnant Women at Tanjung Health Center - Titik Anifah; Anik Purwati; Maria Veronika Widiatrilupi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Anemia in pregnant women is a serious health concern, as red blood cells play a crucial role in delivering essential nutrients and oxygen to the developing fetus. Adequate iron intake during pregnancy is necessary, as maternal anemia is a risk factor for negative perinatal outcomes, such as low birth weight (LBW) and preterm birth. Additionally, anemia during labor can lead to complications, with a 17.24% rate of bleeding directly attributed to this condition. This study aims to explore the relationship between compliance with Fe tablet consumption and the incidence of anemia among pregnant women at the Tanjung Health Center, Tabalong Regency, South Kalimantan. An analytical survey design using a cross-sectional approach was applied, focusing on identifying relationships between two or more variables. The sampling technique employed was total sampling, involving 25 pregnant women, and data was collected using a checklist sheet. Chi-square analysis was performed using SPSS to test the data. The results showed a P-value (asymp. Sig 2-tailed) of 0.000, which is less than 0.05, indicating a significant relationship between Fe tablet consumption compliance and anemia incidence in pregnant women. Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted, concluding that there is a significant relationship between compliance with Fe tablet consumption and the incidence of anemia in pregnant women. This finding highlights the importance of proper iron supplementation in preventing anemia and improving maternal health outcomes during pregnancy.